Optical Property Characterization of Novel Graphene-X (X=Ag, Au and Cu) Nanoparticle Hybrids. (19th November 2013) - Sahu, Sumit Ranjan; Devi, Mayanglambam Manolata; Mukherjee, Puspal; Sen, Pratik; Biswas, Krishanu
Abstract : The present investigation reports new results on optical properties of graphene-metal nanocomposites. These composites were prepared by a solution-based chemical approach. Graphene has been prepared by thermal reduction of graphene oxide (GO) at 90°C by hydrazine hydrate in an ammoniacal medium. This ammoniacal solution acts as a solvent as well as a basic medium where agglomeration of graphene can be prevented. This graphene solution has further been used for functionalization with Ag, Au, and Cu nanoparticles (NPs). The samples were characterized by X-ray diffraction (XRD), Raman spectroscopy, UV-Vis spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) to reveal the nature and type of interaction of metal nanoparticles with graphene. The results indicate distinct shift of graphene bands both in Raman and UV-Vis spectroscopies due to the presence of the metal nanoparticles. Raman spectroscopic analysis indicates blue shift of D and G bands in Raman spectra of graphene due to the presence of metal nanoparticles except for the G band of Cu-G, which undergoes red shift, reflecting the charge transfer interaction between graphene sheets and metal nanoparticles. UV-Vis spectroscopic analysis also indicates blue shift of graphene absorption peak in the hybrids. The plasmon peak position undergoes blue shift in Ag-G, whereas red shift is observed in Au-G and Cu-G.